2019
DOI: 10.1161/str.50.suppl_1.wp314
|View full text |Cite
|
Sign up to set email alerts
|

Abstract WP314: Baltimore City Acute Stroke EMS Routing Pilot Study

Abstract: Introduction: New EMS routing protocols are being proposed to divert acute stroke patients, based on the likelihood of having a large vessel occlusion (LVO), directly to Comprehensive Stroke Centers (CSC), in order to reduce the inherent delay of a secondary transfer from a Primary Stroke Center (PSC) to a CSC. Within Baltimore City, transfer from a PSC to a CSC for mechanical thrombectomy (MT) adds, on average, an additional 90-minute delay in achieving reperfusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…An observational restrospective study of prospective acquired data during the pilot revealed 45/203 (22%) of eligible patients were rerouted, and of those, 20/45 (44%) had ischemic stroke and half of these had an intervention (IVT, MT or both). There were also 10/45 (22%) patients with intracerebral hemorrhage (ICH) that bypassed PSCs, which typically are transferred from PSCs to CSCs ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…An observational restrospective study of prospective acquired data during the pilot revealed 45/203 (22%) of eligible patients were rerouted, and of those, 20/45 (44%) had ischemic stroke and half of these had an intervention (IVT, MT or both). There were also 10/45 (22%) patients with intracerebral hemorrhage (ICH) that bypassed PSCs, which typically are transferred from PSCs to CSCs ( 25 ).…”
Section: Introductionmentioning
confidence: 99%